1994
DOI: 10.1002/ajmg.1320490210
|View full text |Cite
|
Sign up to set email alerts
|

An infant with double trisomy (48,XXX, + 18)

Abstract: We report on an infant with double trisomy 48,XXX, + 18. She presented with manifestations of trisomy 18: prominent occiput, microphthalmia, small mouth, micrognathia, malformed ears, congenital heart defect, overlapping fingers, talipes equinovarus, and rockerbottom feet. An extra palmar crease was present only on the right hand. This patient was alive at 12 months. The clinical manifestations are compared with those of 10 previously reported cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
4
7
0
Order By: Relevance
“…Double autosomal/gonosomal aneuploidy, as was found in the present case, has been described before, i.e., involving trisomy 8, 18, or 21 (DeBrasi et al, 1995;Jaruratanasirikul and Jinorose, 1994; Stevens et al, 1995). Even three cases of a sex chromosome tetrasomy with an additional autosomal trisomy (8 or 18) have been reported (Sutherland et al, 1978;Kardon et al, 1980;Webb et al, 1984).…”
Section: Discussionsupporting
confidence: 81%
“…Double autosomal/gonosomal aneuploidy, as was found in the present case, has been described before, i.e., involving trisomy 8, 18, or 21 (DeBrasi et al, 1995;Jaruratanasirikul and Jinorose, 1994; Stevens et al, 1995). Even three cases of a sex chromosome tetrasomy with an additional autosomal trisomy (8 or 18) have been reported (Sutherland et al, 1978;Kardon et al, 1980;Webb et al, 1984).…”
Section: Discussionsupporting
confidence: 81%
“…However, we verified the presence of some few reported findings. Micropthalmia, corneal opacities and cataractous changes, features verified in our study, were occasionally reported, especially in older studies, published in 1960's and 1970's and in some journals not indexed to PubMed [Calderone et al, ; Jaruratanasirikul and Jinorose, ; Mataftsi et al, ; Acar et al, ].…”
Section: To the Editorsupporting
confidence: 84%
“…The patient had clinical manifestations similar to those of the previously reported 11 cases [Jaruratanasirikul and Jinorose, 1994 for references]. These included severe intrauterine growth retardation, peculiar facial appearance, congenital heart defects, overlapping fingers, rocker-bottom feet, and short life span.…”
supporting
confidence: 71%